The Productivity Analysis of Heavy Equipment Usage in Cut and Fill Work for the IKN Toll Road Construction Project Section 1B, Bandara Sepinggan – Balsam Toll Segment - Dedy Sulistianto; Tatag Yufitra Rus; Mahfud Mahfud (Civil Engineering Dept, Balikpapan State Polytechnics, 2025)
Cut and fill work is a critical initial stage in toll road construction, including the IKN Toll Road Project Section 1B spanning the Bandara Sepinggan – Balsam Toll segment. The effective use of heavy equipment is a key factor influencing the speed and quality of earthwork operations in this project. This study aims to analyze the productivity of excavators, dump trucks, and bulldozers, as well as determine the optimal number of heavy equipment units based on actual operational conditions in the field. A quantitative research method was employed by collecting primary data such as cycle time and equipment efficiency, along with secondary data including equipment capacity and production targets. The results indicate that excavators with bucket capacities of 0.93 m³ and 1.4 m³ have similar productivity levels of approximately 100 m³/hour, requiring nine units each. Dump trucks with capacities of 22 m³ and 10 m³ produce 32.73 m³/hour and 29.03 m³/hour, with required units of 26 and 30, respectively. The bulldozer shows a productivity of 93.2 m³/hour requiring five units. The findings highlight that productivity is influenced not only by equipment capacity but also by cycle time and operational efficiency. The study concludes that planning based on actual field data is crucial for determining the required heavy equipment efficiently and preventing resource inefficiencies.